How a Remote Video Game Coding Camp Improved Autistic College Students' Self-Efficacy in Communication - Begel, Andrew; Dominic, James; Phillis, Conner; Beeson, Thomas; Rodeghero, Paige (The 52nd ACM Technical Symposium on Computer Science Education, 2021)
Communication and teamwork are essential skills for software developers. However, these skills are often difficult to learn for students with autism spectrum disorder (ASD). We designed, developed, and ran a 13-day, remote video game coding camp for incoming college first-year students with ASD. We developed instructional materials to teach computer programming, video game design, and communication and teaming skills. Students used the MakeCode Arcade development environment to build their games and Zoom to remotely collaborate with their teammates. In summative interviews, students reported improved programming skills, increased confidence in communication, and better experiences working with others. We also found that students valued the opportunity to practice teaming, such as being more vocal in expressing ideas to their peers and working out differences of opinion with their teammates. Two students reported the remote learning environment decreased their anxiety and stress; both are frequent challenges for autistic people. We plan to rerun the camp next year with materials that we have made available online.